PELATIHAN TEKNIK PELAPISAN LOGAM DENGAN METODE ELEKTROPLATING UNTUK INDUSTRI KERAJINAN LOGAM DI KAMASAN - PRIAMBADI PRIAMBADI; NITYA SANTHIARSA; SUARNADWIPA SUARNADWIPA; BANDEM ADNYANA (Buletin Udayana Mengabdi, 2007)
ABSTRACT Electroplating is a metal or non-metal coating process with electrolyze that use direct current (DC) and electrolyte (chemical solution) that has a function as medium to supply metal ions. The function of electroplating are protecting metal from corrotion attack, adding surface hardness and improving quality of metal surface. Electroplating process basically has four steps; cleaning, washing, coating and protecting. For a quality result, the coating process need a right and optimum condition of operation, such as, a right concentration of electrolyte, a right voltage or current, and a right temperature.